The way of the white fields in Rhodesia a survey of Christian enterprisein Northern and Souther Rhodesia - Smith, Edwin William, 1876-1957 (London, UK World Dominion, 1928)
World Dominion series
Keywords: Missions -- Rhodesia, Northern; Missions -- Rhodesia, Southern; Missions -- Zambia; Missions -- Zimbabwe